Formulation and Evaluation of Microsponges Gel of Havan Ash for the Treatment of Acne - Syal, Sonali; Pandit, Vinay; Ankalgi, Amar Deep; Verma, C.P.S; Ashawat, M.S. (Journal of Drug Delivery and Therapeutics, 2020)
The aim of this study was to develop the Microsponges containing Havan ash composed gel formulation for the treatment of Acne. Therefore, the topical formulation containing microsponges of Havan Ash will be formulated and evaluated. The preliminary investigation was carried out for the formulation of Havan ash loaded Microsponges by using quasi emulsion solvent diffusion method (MSF1-MSF6). In the preformulation studies of Havan ash the physical description and organoleptic properties, pH, acid insoluble ash, water-soluble ash, IR spectroscopy, identification test, rheological study, atomic absorption spectroscopy is also carried out. On the basis of particle size analysis of Microsponges, percentage yield formulation MSF5 containing Microsponges formula was selected for composition of topical gel formulation. Thus the different gel base formulation (G1-G3) using Carbopol-934 (1,1.5,2.0%) was prepared by emulsification method. By considering all the relevant, physicochemical parameters, G2 gel base was selected for further loading of Havan ash containing Microsponges. The MSF5 formulation was loaded into the selected gel base G2 (1.5%). Then the formulation and evaluation of Havan ash microsponges loaded gel was done. The formulation F3 has better results than other 4 formulations. F3 have its appearance silver colour, consistency very good, Grittiness –ve, homogeneity good, wash ability very good, pH 6.3, Spreadabilty (g.cm/sec) 14.4 ± 0.77 7and viscosity (cps) 18251 ± 50.12, have good result of psychometric analysis. With the revealed results by different evaluation parameters, it is concluded that microsponges drug delivery system has become highly competitive and rapidly evolving technology and more research are carrying out to optimize cost-effectiveness and efficacy of the therapy. Keywords: Havan ash, Antimicrobial, Microsponges, Acne vulgaris, Topical gel.